2015
DOI: 10.1097/shk.0000000000000304
|View full text |Cite
|
Sign up to set email alerts
|

Sepsis Attenuates the Anabolic Response to Skeletal Muscle Contraction

Abstract: Electrically stimulated muscle contraction is a potential clinical therapy to treat sepsis-induced myopathy; however, whether sepsis alters contraction-induced anabolic signaling is unknown. Polymicrobial peritonitis was produced by cecal ligation and puncture (CLP) in male C57BL/6 mice and time-matched, pair-fed controls (CON). At ~24 h post-CLP, the right hindlimb was electrically stimulated via the sciatic nerve to evoke maximal muscle contractions and the gastrocnemius was collected 2 h later. Protein synt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 33 publications
0
15
0
Order By: Relevance
“…Experimental design. Polymicrobial peritonitis was induced using CLP, and separate groups of mice were studied in the acute phase of sepsis (i.e., 24 h post-CLP) (54) or during the recovery phase (i.e., 10 days post-CLP) (60). Briefly, mice were anesthetized with isoflurane (3-4% induction with 2-3% maintenance, Vedco, St. Joseph, MO) in 100% O 2.…”
Section: Methodsmentioning
confidence: 99%
“…Experimental design. Polymicrobial peritonitis was induced using CLP, and separate groups of mice were studied in the acute phase of sepsis (i.e., 24 h post-CLP) (54) or during the recovery phase (i.e., 10 days post-CLP) (60). Briefly, mice were anesthetized with isoflurane (3-4% induction with 2-3% maintenance, Vedco, St. Joseph, MO) in 100% O 2.…”
Section: Methodsmentioning
confidence: 99%
“…Although previously we have reported that sepsis increases REDD1 (48), the causal contribution of this increase to the reduction in mTORC1 signaling and protein synthesis is unknown. Therefore, mice with a global deletion of REDD1 were used to test the hypothesis that elimination of REDD1 would ameliorate the sepsis-induced inhibition of mTORC1 and thereby antagonize the impairment in protein synthesis and contribute to improved survival.…”
mentioning
confidence: 97%
“…Cecal ligation and puncture (CLP) was used to produce sepsis and was performed as described previously (48). Mice were anesthetized (isoflurane, 2-3% in O2 with 1.5% maintenance), and the abdomen was shaved and aseptically prepared.…”
Section: Animalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using cecal ligation and puncture (CLP) as an acute mouse model of sepsis, it was shown that REDD1 protein was increased in the gastrocnemius of male mice along with a decrease in protein synthesis independent of changes in mTORC1 signaling (119). Interestingly, the increase in REDD1 was not offset by a bout of stimulated muscle contractions (ϳ18 h post-sepsis induction and 2 h prior to muscle collection), showing that sepsis rendered REDD1 unresponsive to this significant anabolic stimulus compared with the control condition in which REDD1 protein was reduced by muscle contractions (119).…”
Section: E162mentioning
confidence: 99%